Knowledge of the Corporate Social Responsibility Concept as a Part of the Intellectual Capital of Small and Medium-sized Organizations from the Perspective of Lifelong Learning - Tetiana Arkhangelska, Dana Bernardová, Martin Fink, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The concept of corporate social responsibility (CSR) can be understood as a part of the intellectual capital (IC) of organizations, as a set of tacit knowledge of CSR holders transferred into the form of explicit knowledge recorded in the documents of organizations. The aim of this study, in terms of lifelong learning, is to determine whether CSR is a part of the IC, whether the knowledge of the CSR concept is of a tacit or explicit nature and to what extent the potential of such knowledge is used by small and medium-sized organizations (SMEs). The presented data are a selection taken from 3 studies carried out by the authors in 2014-2019. The study was conducted in the Olomouc region, SMEs were the respondents, and the content of the study referred to CSR. The data show that a tacit form of knowledge of the CSR concept prevails.